1997
DOI: 10.1038/sj.onc.1200886
|View full text |Cite
|
Sign up to set email alerts
|

PCNA: structure, functions and interactions

Abstract: Proliferating cell nuclear antigen (PCNA) plays an essential role in nucleic acid metabolism as a component of the replication and repair machinery. This toroidalshaped protein encircles DNA and can slide bidirectionally along the duplex. One of the wellestablished functions for PCNA is its role as the processivity factor for DNA polymerase d and e. PCNA tethers the polymerase catalytic unit to the DNA template for rapid and processive DNA synthesis. In the last several years it has become apparent that PCNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
563
0
21

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 812 publications
(602 citation statements)
references
References 81 publications
(156 reference statements)
18
563
0
21
Order By: Relevance
“…7 -9 CDK2 is the catalytic partner of two cyclins involved in S phase progression, cyclin A and E, whereas PCNA plays an essential role in DNA replication as an auxiliary protein of Pol , the enzyme responsible for the replication of chromosomal DNA. In vitro studies have shown that p21 inhibits processive DNA synthesis through a PCNA -dependent mechanism 48 and the formation of Cancer Gene Therapy p21/E2F-1 gene therapy in colon cancer MJ Elliott et al cyclin-CDK complexes. 19 -24 Recently, much attention has been focused on the CDK2 -and PCNA -binding domains of p21 and their importance in facilitating G1 and G2 cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…7 -9 CDK2 is the catalytic partner of two cyclins involved in S phase progression, cyclin A and E, whereas PCNA plays an essential role in DNA replication as an auxiliary protein of Pol , the enzyme responsible for the replication of chromosomal DNA. In vitro studies have shown that p21 inhibits processive DNA synthesis through a PCNA -dependent mechanism 48 and the formation of Cancer Gene Therapy p21/E2F-1 gene therapy in colon cancer MJ Elliott et al cyclin-CDK complexes. 19 -24 Recently, much attention has been focused on the CDK2 -and PCNA -binding domains of p21 and their importance in facilitating G1 and G2 cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…We used PCNA, a DNA replication processivity factor, as a marker. Upon progression of S-phase most of the PCNA pool changes its localization from bulk chromatin to the nucleoli and from euchromatin to heterochromatin (Kelman, 1997). Double immunofluorescent staining of an asynchronous population of NIH3T3 cells demonstrated that pW29 does not relocate with PCNA (Fig.…”
Section: Expression and Intracellular Localization Of The Msmcb Msmcmentioning
confidence: 94%
“…PCNA is a processivity factor of DNA polymerase d (pol d), an enzyme involved in both DNA replication and NER (Kelman, 1997). Excess PCNA has been shown to promote DNA synthesis past template lesions (Mozzherin et al, 1996(Mozzherin et al, , 1997.…”
Section: Effect Of Tax On Cellular Dna Repairmentioning
confidence: 99%